Assessment of the acquisition of executive function during the transition from adolescence to adulthood in male and female mice - Ryan Shepard; Emily Beckett; Laurence Coutellier (Developmental Cognitive Neuroscience, 2017)
Executive functions (EF) reached full maturity during the transition from adolescence to adulthood. Human studies provide important information about adolescent developmental trajectories; however, little remains known about the neural circuits underlying the acquisition of mature EF. Ethical and technical considerations with human subjects limit opportunities to design experimental studies that allows for an in-depth understanding of developmental changes in neural circuits that regulate cognitive maturation. Preclinical models can offer solutions to this problem. Unfortunately, current rodent models of adolescent development have inherent flaws that limit their translational value. For instance, females are often omitted from studies, preventing the assessment of potential sex-specific developmental trajectories. Furthermore, it remains unclear whether cognitive developmental changes in rodents are similar to those observed in humans. Here, we tested adolescent and adult male and female mice in a neurocognitive battery of assays. Based on this approach, we assessed mice performances within distinct subdomains of EF, and observed similarities with human developmental trajectories. Furthermore, the sex-specific cognitive changes we observed were paralleled by molecular and neural activity changes demonstrating that our approach can be used in future research to assess the contribution of precise neural circuits to adolescent cognitive maturation. Keywords: Executive functions, Adolescence, Prefrontal cortex, Striatum, Mice